Genesis of Ultramafic Lamprophyres and Carbonatites at Aillik Bay, Labrador: a Consequence of Incipient Lithospheric Thinning beneath the North Atlantic Craton - TAPPE, SEBASTIAN; FOLEY, STEPHEN F.; JENNER, GEORGE A.; HEAMAN, LARRY M.; KJARSGAARD, BRUCE A.; ROMER, ROLF L.; STRACKE, ANDREAS; JOYCE, NANCY; HOEFS, JOCHEN (Journal of Petrology, 2006)
Numerous dykes of ultramafic lamprophyre (aillikite, mela-aillikite, damtjernite) and subordinate dolomite-bearing carbonatite with U-Pb perovskite emplacement ages of ∼590-555 Ma occur in the vicinity of Aillik Bay, coastal Labrador. The ultramafic lamprophyres principally consist of olivine and phlogopite phenocrysts in a carbonate- or clinopyroxene-dominated groundmass. Ti-rich primary garnet (kimzeyite and Ti-andradite) typically occurs at the aillikite type locality and is considered diagnostic for ultramafic lamprophyre-carbonatite suites. Titanian aluminous phlogopite and clinopyroxene, as well as comparatively Al-enriched but Cr-Mg-poor spinel (Cr-number < 0.85), are compositionally distinct from analogous minerals in kimberlites, orangeites and olivine lamproites, indicating different magma geneses. The Aillik Bay ultramafic lamprophyres and carbonatites have variable but overlapping 87Sr/86Sr i ratios (0·70369-0·70662) and show a narrow range in initial ε Nd (+0·1 to +1·9) implying that they are related to a common type of parental magma with variable isotopic characteristics. Aillikite is closest to this primary magma composition in terms of MgO (∼15-20 wt %) and Ni (∼200-574 ppm) content; the abundant groundmass carbonate has δ13C PDB between -5·7 and -5‰, similar to primary mantle-derived carbonates, and δ18O SMOW from 9·4 to 11·6‰. Extensive melting of a garnet peridotite source region containing carbonate- and phlogopite-rich veins at ∼4-7 GPa triggered by enhanced lithospheric extension can account for the volatile-bearing, potassic, incompatible element enriched and MgO-rich nature of the proto-aillikite magma. It is argued that low-degree potassic silicate to carbonatitic melts from upwelling asthenosphere infiltrated the cold base of the stretched lithosphere and solidified as veins, thereby crystallizing calcite and phlogopite that were not in equilibrium with peridotite. Continued Late Neoproterozoic lithospheric thinning, with progressive upwelling of the asthenosphere beneath a ...